PP.16.02: COMPARISON OF ANTHROPOMETRIC INDICES AS PREDICTORS OF CARDIOVASCULAR DISEASE RISK FACTORS IN PORTUGUESE ADULT POPULATION. (June 2015) - Borges, S; Mendonca, M.I.; Pereira, A.; Rodrigues, R.; Gomes, S.; Oliveira, R.; Sousa, A.C.; Henriques, E.; Rodrigues, M.; Ornelas, I.; Pereira, D.; Reis, R. Palma dos
Abstract : Objective: Obesity is associated with diabetes mellitus, hypertension, dyslipidemia and increased cardiovascular disease (CVD) risk. Anthropometric indeces, such body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR), were evaluated as predictors of the presence of CVD risk factors in Portuguese adults. Design and method: The study contained a 2555 representative sample of Portuguese adults 1952 male aged 52.5 ± 8.2 years and 603 female aged 53.5 ± 8.8 years. All anthropometric indices correlated significantly with fasting glucose level, systolic and diastolic Blood Pressure, Tryglicerides and inversely with the high-density lipoprotein (HDL-C) level (p < 0.0001). Results: The WHtR showed higher correlation with CVD risk factors than WC and BMI in both men (p < 0.0001, r correlation of 0.21, 0.20, 0.18, 0.15 and -0.2 respectively) and female (P < 0.0001, 0.28, 0.27, 0.24 0.3, -0.37). Regarding Diabetes, Hypertension and Low HDL-C the area under the receiver (AUCs) operating characteristic (ROC) curve for WHtR was higher than that for WC or BMI in the male group. In female group the ROC curve increased from the BMI to WC, beeing highest for WHtR. WC was a better predictor for High cholesterol and LDL in men. The AUCs for WHtR were highest for Diabetes (AUC = 0.74 and Hypertension (AUC = 0.74) in female group and male group (AUC = 0.66 and AUC = 0.68). The WHtR cut-off value to predict diabetes mellitus, hypertension, and dyslipidemia was approximately 0.57 in men and 0.58–0.62 in women. The WC cut-offs varied from 92 to 101 cm in men and from 88 to 97 cm in women. The optimal BMI cut-off point varied from 21.7 to 29.1 kg/m 2 in women and from 26 to 29 Kg/m 2 in men. Conclusions: WC or WHtR were better predictors of CVD risk factors than BMI in Portuguese Adult Population.